The Study On The Ability Of The Pharmacy Faculty Students Of UMS In Understanding Drug Labels - Susiati, Susiati (2004)
The objective of this study is to know the ability of the second semester students of Pharmacy Faculty in understanding drug labels. The method used in this research is descriptive method, which emphasizes the discription of the students' ability in understanding drug labels. The writer takes 40 students at the second semester students in 2002-2003 as the sample. In getting the sample, the writer uses random sampling where every member of population has the same opportunity to member the sample. To get data, the writer gives a test to the students. The steps taken by the writer in analyzing the data are score, tabulating, and looking for the percentage with the category: very good, good, fair, and poor. Based on the data analysis, the writer concludes that the second semester students of Pharmacy Faculty in UMS dot not get difficulties in understanding drug labels.